2018
DOI: 10.1080/03009742.2017.1397188
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for orthopaedic surgery in patients with rheumatoid arthritis: results from a retrospective cohort study of 1010 patients diagnosed from 1972 to 2009 and followed up until 2015

Abstract: Patients with a diagnosis in the early years had a greatly increased risk of having orthopaedic surgery performed. This is probably due to the year of diagnosis being a proxy for the type and intensity of medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
2
2
0
1
Order By: Relevance
“…In contrast, another cohort study [34] did not mention BMI ≥ 30 kg/m 2 as a predictive factor for orthopedic surgeries among these patients. Another investigation also demonstrated that high BMI is associated with increased total knee arthroplasty in RA patients [35]. In addition, our results showed that the mean age and BMI of patients with any surgery history were higher than those without surgery.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, another cohort study [34] did not mention BMI ≥ 30 kg/m 2 as a predictive factor for orthopedic surgeries among these patients. Another investigation also demonstrated that high BMI is associated with increased total knee arthroplasty in RA patients [35]. In addition, our results showed that the mean age and BMI of patients with any surgery history were higher than those without surgery.…”
Section: Resultssupporting
confidence: 73%
“…Decreased physical activity can lead to obesity and high BMI [36], which can exacerbate the inflammatory process and destruction of joints, such as affected knees in RA patients. It can increase the risk of orthopedic surgeries [33,35]. Furthermore, orthopedic surgeries were more prevalent in housekeepers than the others in our study.…”
Section: Resultsmentioning
confidence: 65%
“…Treatment with methotrexate and biologics is associated with a lower risk of cardiovascular events [13][14][15][16][17]. The increased use of methotrexate and biologics over time is evident in our cohort as shown in a previous study, and could explain the low AMI and IHD risk seen in RA patients diagnosed after 1998 [37]. Probably, the improved drugs and treatment strategies have reduced in ammation-driven atherosclerosis su ciently to render the IHD risk similar to the general population.…”
Section: Discussionsupporting
confidence: 64%
“…A artrite inflamatória provocada pela AR causa deformidades articulares principalmente nos pés e nas mãos, gerando incapacidades e redução da qualidade de vida de portadores desta doença (2,10) . Mesmo com o surgimento de novos medicamentos para o controle desta morbidade, que provocou um declínio no número de intervenções ortopédicas, ainda se encontra um número considerável de indivíduos portadores de AR com deformidades nos pés (18) . Em nossa amostra 80% era do sexo feminino, com idade média de 71anos, sendo que esta prevalência de AR acompanha os dados da literatura (15) .…”
Section: Discussionunclassified